2012
DOI: 10.1021/ma301000z
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Lamellar Structures Near the Polymer/Substrate Interface

Abstract: We report the structural heterogeneity of recrystallized linear low-density polyethylene (LLDPE) films (25, 50, and 100 nm in thickness) in the direction normal to the surface, based on in situ grazing incidence small-angle X-ray scattering (GISAXS) and X-ray diffraction (GID) measurements. The GID results have clarified the presence of the edge-on lamellae at the surfaces and in the interior of the LLDPE films prepared on Si substrates as thin as 25 nm in thickness. However, the degree of the crystallinity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 55 publications
1
54
0
Order By: Relevance
“…Figure illustrates the crystalline morphology for two films with different interfacial interactions ( B / E c = 0 and −2.8, respectively) at 200 000 MC cycles. Edge‐on crystals with stems in parallel with the film surface can be observed in the film with an interfacial interaction of B / E c = 0, which is consistent with the experimental findings . Using molecular dynamics simulations, Luo et al also observed the crystalline stems aligned parallel to substrates .…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Figure illustrates the crystalline morphology for two films with different interfacial interactions ( B / E c = 0 and −2.8, respectively) at 200 000 MC cycles. Edge‐on crystals with stems in parallel with the film surface can be observed in the film with an interfacial interaction of B / E c = 0, which is consistent with the experimental findings . Using molecular dynamics simulations, Luo et al also observed the crystalline stems aligned parallel to substrates .…”
Section: Resultssupporting
confidence: 73%
“…Besides, Asada et al . demonstrated the occurrence of heterogeneous nucleation initiated from the polymer–substrate interface . Figure depicts the changes in the number of crystalline bonds in the interfacial regions (the Z = 2 and Z = 5 layers) during crystallization for systems with different interfacial interactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations